Quantum Effects in Silicon Carbide Hold Promise for Novel Integrated Devices and Sensors. Issue 9 (7th August 2013) - Castelletto, Stefania; Johnson, Brett C.; Boretti, Alberto
<x xml:space="preserve">Abstract</x> Silicon carbide (SiC) offers a unique opportunity to realize advanced quantum‐based devices and sensors. The role of paramagnetic defects in this material to achieve optical and spin quantum coherence control are discussed, and SiC nanostructures exhibiting optical emission due to quantum confinement associated with size reduction and bandgap engineering are reviewed. The combination of nanostructures and in‐built paramagnetic defects in SiC could pave the way for future single‐particle and single‐defect quantum devices and related biomedical sensors. Relevant classical devices in SiC (photonic crystals, nanocantilevers, microdisks) that could be integrated with intrinsic defects to achieve further functionalities in these systems are also reviewed, and an outlook is provided on future sensors that could arise from the integration of paramagnetic defects in SiC nanostructures and devices.